Evaluating implementation of the International Classification of Functioning, Disability and Health in Portugal's special education law - Sanches-Ferreira, Manuela (2019)
This paper reports the results of a national two-year project, commissioned by the Portuguese Ministry of Education, to investigate the implementation of the International Classification of Functioning, Disability and Health (ICF) under Decree-Law 3/2008. The Decree-Law also introduced the principle that the documentation of students' functioning profiles should be the basis for eligibility decision-making – replacing the need of a diagnosis. Of specific interest was the study of the ICF implementation in the assessment, eligibility and intervention processes of students in need of specialised supports. To that end, the study was based on a document analysis of case records of 214 students. The analysis of functioning profiles showed that the ICF use promoted a functional approach in students' assessment. In addition, the use of the ICF contributed to the differentiation of eligible and non-eligible students based on their functioning profiles and addressed the most suitable educational interventions within the Individualised Education Plans.